A Four Carbon Organonitrate as a Significant Product of Secondary Isoprene Chemistry. Issue 11 (26th May 2022) - Tsiligiannis, Epameinondas; Wu, Rongrong; Lee, Ben H.; Salvador, Christian Mark; Priestley, Michael; Carlsson, Philip T. M.; Kang, Sungah; Novelli, Anna; Vereecken, Luc; Fuchs, Hendrik; Mayhew, Alfred W.; Hamilton, Jacqueline F.; et al.
Abstract: Oxidation of isoprene by nitrate radicals (NO3 ) or by hydroxyl radicals (OH) under high NOx conditions forms a substantial amount of organonitrates (ONs). ONs impact NOx concentrations and consequently ozone formation while also contributing to secondary organic aerosol. Here we show that the ONs with the chemical formula C4 H7 NO5 are a significant fraction of isoprene‐derived ONs, based on chamber experiments and ambient measurements from different sites around the globe. From chamber experiments we found that C4 H7 NO5 isomers contribute 5%–17% of all measured ONs formed during nighttime and constitute more than 40% of the measured ONs after further daytime oxidation. In ambient measurements C4 H7 NO5 isomers usually dominate both nighttime and daytime, implying a long residence time compared to C5 ONs which are removed more rapidly. We propose potential nighttime sources and secondary formation pathways, and test them using a box model with an updated isoprene oxidation scheme. Plain Language Summary: Isoprene is the most abundant non‐methane trace gas emitted from vegetation in the atmosphere. Isoprene reacts with different oxidants forming numerous multifunctional products that affect both ozone and particulate matter concentrations via secondary organic aerosol formation. Day and nighttime isoprene oxidation under polluted conditions with high levels of nitrogen oxides (NOx ) produces nitrogen containing species. Here, we used state‐of‐the‐art instrumentation to measure the isoprene‐derived nitrogen‐containing species, both in laboratory experiments and at six field sites around the globe. To support our interpretation, we apply a recently developed model for nighttime isoprene chemistry. We have identified a dominant nitrated product(s) in our experiments and with a significant ambient contribution both during day and nighttime. Key features of this species are its secondary formation from primary products and its relatively long lifetime under ambient conditions, explaining its accumulation in the atmosphere. Thus, it can be an important marker for the influence of NOx on isoprene oxidation. Key Points: The C4 H7 NO5 isomers are major secondary products of isoprene oxidation during nighttime and daytime in NOx ‐influenced regions The C4 H7 NO5 isomers are multi‐generational products from several C5 compounds that accumulate in the atmosphere C4 H7 NO5 as a dominant isoprene‐derived species, can be important for the formation of ozone